1958
DOI: 10.2337/diab.7.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Glucagon Administration in the Cat and Dog

Abstract: It has been postulated that glucagon, the hyperglycemic factor of the pancreatic a-cells, plays an important role in the pathogenesis of diabetes mellitus in man. 1 ' 2 This hypothesis suggests that an excessive secretion of glucagon in relation to insulin results in the diabetic state and is based on the finding of an increased a/P-cell ratio in the pancreatic islets of diabetic patients. One reason that the concept remains controversial is that efforts to induce permanent diabetes in the rat and the rabbit w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1959
1959
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…These animals experienced hyperglycemia for 1–3 hours following each single glucagon injection, and sustained hyperglycemia if receiving a CRI. All animals returned to baseline serum glucose concentrations following discontinuation of the glucagon, and there were no toxic effects, weight loss, or prolonged hyperglycemia noted with long‐term administration of glucagon . A more recent study comparing glucagon administration by subcutaneous and intravenous injection found significant increases in glucose concentrations 10, 20, and 30 minutes following administration .…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…These animals experienced hyperglycemia for 1–3 hours following each single glucagon injection, and sustained hyperglycemia if receiving a CRI. All animals returned to baseline serum glucose concentrations following discontinuation of the glucagon, and there were no toxic effects, weight loss, or prolonged hyperglycemia noted with long‐term administration of glucagon . A more recent study comparing glucagon administration by subcutaneous and intravenous injection found significant increases in glucose concentrations 10, 20, and 30 minutes following administration .…”
Section: Discussionmentioning
confidence: 77%
“…discontinuation of the glucagon, and there were no toxic effects, weight loss, or prolonged hyperglycemia noted with long-term administration of glucagon. 13 A more recent study comparing glucagon administration by subcutaneous and intravenous injection found significant increases in glucose concentrations 10, 20, and 30 minutes following administration. 11 Significantly higher BG values were noted following intravenous administration compared to subcutaneous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations